In-silico modeling of SARS-CoV-2 replication-transcription complex for inhibition studies - Notsonono, Anovuyo (Rhodes University, 2026)
Since the emergence of SARS-CoV-2, the causative agent of COVID-19 in Wuhan, China, in 2019, millions of people have died, motivating extensive research into antiviral therapies against this virus. Despite significant progress, current treatments remain insufficient due to adverse effects and limited efficacy. Most studies have focused on structural proteins, with some attention given to non-structural proteins such as nsp12. However, the emergence of new viral variants highlights the need for alternative therapeutic approaches. This study explores the replication-transcription complex (RTC), comprising of non-structural proteins nsp7, nsp8, nsp12, and nsp13, as a potential target for antiviral therapies. This complex is crucial for the survival of the virus as it is responsible for RNA synthesis. A total of 56,618 compounds were virtually screened to identify potential inhibitors of nsp13. PF-03715455, a compound with previously reported antiviral activity, was used as a reference. Several compounds demonstrated strong binding to the ATP binding site of nsp13, with BPMPSPzP, CPMP-PyMP, DCP-EPP, and BCIA emerging as the most promising lead candidates. In parallel to that, 1215 aptamers were designed and screened against the RTC, with aptamers AP1 and AP2 showing the highest binding affinity. Molecular dynamics simulations were conducted on the lead compounds and aptamers bound to the RTC for 50 ns to investigate their effect on the stability and dynamics on the RTC. Additionally, to enhance these findings, umbrella sampling simulations were conducted on the RTC-BPMPS-PzP system to refine insights into the binding dynamics and free-energy landscape. The results showed a huge potential of these ligands and aptamers as inhibitors of the RTC. The results also highlighted the utility of Umbrella sampling in studies of this nature and also underscored the suitability of aptamers as antiviral therapies targeting the RTC, thus making this approach worth exploring in future studies. These results, together with the ease of design and availability of these small molecules and aptamers, thus warrant further investigation into their inhibitory potential.
Keywords: Uncatalogued